Multimedia in high school mathematics classes: Students' perceptions of the learning environment and engagement - Chipangura, Addwell Tichafa (Curtin University, 2014)
This study examined whether students in classes frequently exposed to multimedia in mathematics differed in terms of their perceptions of the learning environment and levels of engagement from their counterparts who were not. The results indicated that students in classes frequently exposed to multimedia viewed the learning environment more positively and were more engaged than their counterparts who were not. These findings offer important insights into how exposure to multimedia could promote engagement in mathematics.